Hubungan Disposisi Matematis dengan Kemampuan Pemecahan Masalah pada Mata Pelajaran Matematika - Rezita, Riva; Rahmat, Tasnim (Lattice Journal : Journal of Mathematics Education and Applied, 2022)
The purpose of this research is to determine whether or not there is a significant relationship between mathematical disposition and problem-solving abilities in mathematics in class XI science students at SMAN 2 Bukittinggi in 2020/2021. This type of research is correlational research. The population in this study were all students of class XI IPA SMAN 2 Bukittinggi as many as 4 classes totaling 140 students. The sample in this study were 21 students who were taken randomly. The instrument used is a mathematical disposition questionnaire and a problem-solving ability test on mathematics subjects filled out by the respondents. From the results of data analysis obtained F_count > F_table which is 17.37 > 3.57 so that the data of mathematical disposition towards solving mathematical problems has a linear pattern. The strength of the relationship is shown by the correlation coefficient rcount = 0.691. This means that there is a strong and significant positive relationship between mathematical disposition and problem-solving abilities in mathematics in class XI science students at SMAN 2 Bukittinggi in 2020/2021.Tujuan dilaksanakannnya penelitian ini adalah untuk mengetahui ada atau tidaknya hubungan yang signifikan antara disposisi matematis dengan kemampuan pemecahan masalah pada mata pelajaran matematika pada siswa kelas XI IPA di SMAN 2 Bukittinggi tahun 2020/2021. Jenis penelitian ini adalah penelitian korelasional. Populasi dalam penelitian ini adalah seluruh siswa kelas XI IPA SMAN 2 Bukittinggi sebanyak 4 kelas yang berjumlah 140 orang siswa. Sampel dalam penelitian ini adalah sebanyak 21 orang siswa yang diambil secara acak. Instrumen yang digunakan adalah angket disposisi matematis dan soal tes kemampuan pemecahan masalah terhadap mata pelajaran matematika yang diisi oleh responden. Dari hasil analisis data diperoleh    yaitu  >  sehingga data disposisi matematis terhadap pemecahan masalah matematika berpola linier.  Kekuatan hubungan ditunjukkan oleh koefisien korelasi rhitung = 0,691 ini berarti ada hubungan positif yang kuat dan  signifikan antara disposisi matematis dengan kemampuan pemecahan masalah terhadap mata pelajaran matematika pada siswa kelas XI IPA di SMAN 2 Bukittinggi tahun 2020/2021.